Pulp celebrates ten years of panty-dropping music history. ([Manila?] Vernon Go, 2009)
Compilation of Pulp's best features, photo shoots and bands.
Keywords: Popular music -- Philippines -- History and criticism; Rock music -- Philippines -- History and criticism; Popular music -- Pictorial works; Popular music -- Miscellanea; Rock music -- Miscellanea